Banking across borders - Friederike Niepmann (Federal Reserve Bank of New York, 2012)
This paper develops and tests a theoretical model that allows for the endogenous decision of banks to engage in international and global banking. International banking, where banks raise capital in the home market and lend it abroad, is driven by differences in factor endowments across countries. In contrast, global banking, where banks intermediate capital locally in the foreign market, arises from differences in country-level bank efficiency. Together, these two driving forces determine the foreign assets and liabilities of a banking sector. The model provides a rationale for the observed rise in global banking relative to international banking. Its key predictions regarding the cross-country pattern of foreign bank asset and liability holdings are strongly supported by the data.
Keywords: F21; F23; F34; G21; 330; international banking; cross-border lending; capital flows; trade in banking services